Analisis fisik serta sensori kue kering dengan campuran tepung mocaf, oats, dan bekatul - Monika Rahardjo; Kristiawan Prasetyo Agung Nugroho; Greis Saibele (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
This research aims to analyze the physical and sensory characteristics of cookies’ formulations using mocaf-oats-rice bran’s flour mixture. Five formulations used in this research consist of mocaf-oats-rice bran’s flour mixture namely F1 (100%-0%-0%), F2 (70%-15%-15%), F3 (50%-25%-25%), F4 (30%-35%-35%), and F5 (0%-50%-50%). The result showed that all cookies formulation included in the category of “high fiber” except for cookies Formulation 4. The highest value of hardness was cookies Formulation 1 and significantly different from the other formulations. Decreasing mocaf flour composition in the mixture and increasing additional oats and rice bran composition have a significant correlation on cookies’ hardness. Based on sensory evaluation using rating preference, it was found that the highest rating for color, texture, and overall parameters obtained by cookies Formulation 4, while the highest rating for taste parameter obtained by cookies Formulation 5. Cookies’ formulation that recommended to use as utilization of mocaf flour was Formulation 4 because it had the highest rating for overall parameter, as well as highest rating for color and texture.